(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This article aims to introduce the psychological basis of ‘Recognition’ as presented by Axel Honneth. is considered as an important term in occidental philosophy, given its important place in social sciences. we can find some of its most important traits in book confession of Saint Augustine and the philosopher Rousseau, who considered the most important founder of the Recognition speech, and in the work of the German philosopher Hegel, whom established the theoretical framework of this term in his famous book entitled The Phenomenology of Spirit. However, Honneth based his theory on various follow-ups. In addition to the philosophical implications, Honneth merged this term with psychological content that gave it a more robust shape than we might see with Hegel. This psychological reinforcement opened its scope of application to include political, social, anthropological and psychological fields, which in turn we will be addressing in detail.